2017
DOI: 10.3847/1538-4357/835/1/65
|View full text |Cite
|
Sign up to set email alerts
|

Space Telescope and Optical Reverberation Mapping PROJECT.VI. Reverberating Disk Models for NGC 5548

Abstract: We conduct a multiwavelength continuum variability study of the Seyfert 1 galaxy NGC 5548 to investigate the temperature structure of its accretion disk. The 19 overlapping continuum light curves (1158 Å to 9157 Å) combine simultaneous Hubble Space Telescope, Swift, and ground-based observations over a 180 day period from 2014 January to July. Light-curve variability is interpreted as the reverberation response of the accretion disk to irradiation by a central time-varying point source. Our model yields the di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 45 publications
8
87
1
Order By: Relevance
“…CREAMʼs MCMC algorithm also rescales the nominal error bars using an extra variance, V j , and scale factor parameters, f j , for each telescope (Starkey et al 2017). The rescaled error bars are…”
Section: Light Curve Intercalibrationmentioning
confidence: 99%
“…CREAMʼs MCMC algorithm also rescales the nominal error bars using an extra variance, V j , and scale factor parameters, f j , for each telescope (Starkey et al 2017). The rescaled error bars are…”
Section: Light Curve Intercalibrationmentioning
confidence: 99%
“…McHardy et al (2014) resolved continuum lags in this object using two years of Swift data, while the Space Telescope and Optical Reverberation Mapping project (AGN STORM, De Rosa et al 2015) obtained the most complete RM measurement of the accretion disk to date. The STORM project detected interband lags between the X-ray, UV, optical, and near-IR wavelengths using four space-based observatories and 25 ground-based telescopes (Edelson et al 2015;Fausnaugh et al 2016;Starkey et al 2017), and the measured lagwavelength relation is again consistent with predictions for reprocessing in a geometrically thin disk. However, the size of the disk indicated by the STORM measurements is larger by a factor of three than the predictions from standard models.…”
Section: Introductionmentioning
confidence: 59%
“…This poor correlation was also seen in 2013 by Shappee et al (2014), and has been observed in other objects, including NGC 5548 (Uttley et al 2003;Edelson et al 2015), MR 2251-178 (Arévalo et al 2008), Mrk 79 (Breedt et al 2009), NGC 3783 ), and NGC 4151 (Edelson et al 2017). Several of these studies have been unable to represent the UV/optical light curves as a reprocessed (smoothed and shifted) version of the X-ray light curve (Arévalo et al 2008;Breedt et al 2009;Starkey et al 2017), which is problematic for a generic disk reprocessing model. A notable exception is Shappee et al (2014), who were able to produce a good, but not perfect, match between the X-ray and optical light curves from 2013 using a simple reprocessing model for NGC 2617.…”
Section: Challenges To the Disk Reprocessing Modelmentioning
confidence: 94%
“…Reverberating-disk models for NGC 5548 are presented in Paper VI (Starkey et al 2017). As noted in Paper I and discussed in detail in Paper IV (Goad et al 2016), an anomalous behavior of the broad UV emission lines was observed during the campaign.…”
Section: Introductionmentioning
confidence: 77%